No Other Safe Care Option: Nursing Home Admission as a Last Resort Strategy. (26th June 2020) - Campbell-Enns, Heather J; Campbell, Megan; Rieger, Kendra L; Thompson, Genevieve N; Doupe, Malcolm B
Abstract: Background and Objectives: Nursing homes are intended for older adults with the highest care needs. However, approximately 12% of all nursing home residents have similar care needs as older adults who live in the community and the reasons they are admitted to nursing homes is largely unstudied. The purpose of this study was to explore the reasons why lower-care nursing home residents are living in nursing homes. Research Design and Methods: A qualitative interpretive description methodology was used to gather and analyze data describing lower-care nursing home resident and family member perspectives regarding factors influencing nursing home admission, including the facilitators and barriers to living in a community setting. Data were collected via semistructured interviews and field notes. Data were coded and sorted, and patterns were identified. This resulted in themes describing this experience. Results: The main problem experienced by lower-care residents was living alone in the community. Residents and family members used many strategies to avoid safety crises in the community but experienced multiple care breakdowns in both community and health care settings. Nursing home admission was a strategy used to avoid a crisis when residents did not receive the needed support to remain in the community. Discussion and Implications: To successfully remain in the community, older adults require specialized supports targeting mental health and substance use needs, as well as enhanced hospital discharge plans and improved information about community-based care options. Implications involve reforming policies and practices in both hospital and community-based care settings.